Dates and demography? The need for caution in using radiometric dates as a robust proxy for prehistoric population change. Issue 3 (17th April 2016) - Hiscock, Peter; Attenbrow, Val
ABSTRACT: Our paper (Attenbrow and Hiscock 2015) raised serious concerns about the use of radiocarbon dates (sum probability distributions) as evidence of ancient demography. Prominent researchers who commented here and who rely on such interpretations are uncomfortable with our critique, and insist that quantities of dates are a reliable indicator of past population size. Here, we note that while those researchers acknowledge the difficulties of sample selection, taphonomic bias, and the relationship of charcoal and radiocarbon data to human activity, they have not studied or controlled for these matters. At this time, we again advocate caution in the use of dates as data for demographic reconstructions.